Genetic gains from selection for high grain yield and Striga resistance in early maturing maize cultivars of three breeding periods under Stigainfested and Strigafree environments - Badu-Apraku, Baffour; Yallou, C.; Oyekunle, M. (Elsevier, 2013)
Maize is the most important staple cereal crop in sub-Saharan Africa (SSA) and has great potential to rectify the food insecurity in the sub-region. A study was conducted at four locations two each in Nigeria and Benin in 2010 and 2011 to determine the rate of genetic improvement in the grain yield of 50 maize cultivars developed during three breeding periods, 1988–2000 (period 1), 2001–2006 (period 2) and 2007–2010 (period 2) under Striga-infested and Striga-free conditions. Under Striga infestation, mean grain yield ranged from 2537 kg ha?1 for the period 1 cultivars to 3122 kg ha?1 for period 3 cultivars with a corresponding annual genetic gain of 1.93%. When Striga-free, grain yield ranged from 3646 kg ha?1 for the period 1 cultivars to 4227 kg ha?1 for the period 2 cultivars with an annual genetic gain of 1.0%. The average annual rate of increase in grain yield was 41 kg ha?1 when Striga-infested and 34 kg ha?1 when Striga-free. The annual genetic gain in grain yield was 0.86% for period 1 cultivars, 2.07% for period 2 cultivars, and 2.11% for period 3 cultivars under Striga infestation. The increase in grain yield under Striga infestation was associated with significant decrease in Striga damage and the number of emerged Striga plants at 8 and 10 weeks after planting (WAP), an improvement in ear aspect, lodging resistance, plant height, and increase in the number of ears per plant (EPP) from the period 1 to the period 3 cultivars. For the emerged Striga plants, the annual genetic gains of ?0.63% for 8 WAP and ?0.57% for 10 WAP were obtained from the period 1 to the period 2 cultivars. The increase in genetic gains was 0.70% for EPP and ?0.65% for ear aspect. The increase in grain yield from period 1 to period 3 cultivars when Striga-free was associated with increased days to anthesis, increased plant and ear heights, improvement in ear aspect, and husk cover and increased EPP. Cultivars 28, 14, 29, and 26 were the most outstanding across Striga-infested environments. Substantial progress has been made in breeding for high yielding, Striga resistant/tolerant cultivars during the past three decades.